Asset growth and the cross-section of stock returns : evidence from Japan. - Chua, Dennis Wen Ping. (2009)
We test and observe in Japan‟s context a negative correlative between asset growth and abnormal returns. Contrary to previous research by Cooper, Gulen and Schill (2008), we do not observe significant alpha returns upon dividing sample firms into three categories based on market capitalization. Furthermore, the Fama and Macbeth (1973) regression is used to test if asset growth exhibits the same significance and dominance as a strong predictor in explaining the variability of stock returns. The predictive effects of asset growth shown in the US equity markets produce contrasting results when we conduct it in the Japan equity markets.